Secure performance comparison for NOMA: Reconfigurable intelligent surface or amplify-and-forward relay? - Chengjun Jiang; Chensi Zhang; Chongwen Huang; Jiaying He; Zhe Zhang; Jianhua Ge (Journal of Information and Intelligence, 2024)
The amplify-and-forward (AF) relay is widely employed owing to its simplicity, while reconfigurable intelligent surface (RIS) technology is envisioned as the next generation of relay technology due to its high energy efficiency. This paper compares these two technologies at the physical layer security (PLS) level for non-orthogonal multiple access (NOMA) with an internal near-end eavesdropper. Specifically, for a fair comparison, both the number of RIS elements and AF relay antennas are set to N, and similar secure transport strategies are utilized for both models to maximize the secrecy rate. Analytical results demonstrate that the PLS performance of RIS-assisted NOMA is better than that of AF relay-assisted NOMA if N reaches a certain threshold. Simulation results verify the correctness of the theoretical analysis.